Preventive defense : a new security strategy for America - Carter, Ashton B.; Perry, William James, 1927- (Washington, D.C. : Brookings Institution Press, 1999)
"William J. Perry and Ashton B. Carter draw on their experience as leaders of the U.S. Defense Department to propose a new American security strategy for the twenty-first century. After a century in which aggression had to be defeated in two world wars and then deterred through a prolonged cold war, the authors argue for a strategy centered on prevention." "The authors' preventive defense strategy concentrates on the dangers that, if mismanaged, have the potential to grow into true threats to U.S. survival in the next century." "They also argue for better management of the defense establishment so the United States will retain a strong military prepared to cope with all contingencies deter aggressors and win a conflict it deterrence faits."--Jacket.
Four trips to Pervomaysk: preventive defense at work -- Preventive defense -- Pursuing Marshall's vision with Russia and NATO -- Project Sapphire, the Nunn-Lugar program, and arms control -- Dealing with a rising China -- Standing at the brink in North Korea: the counterproliferation imperative -- A false alarm (this time): preventive defense against catastrophic terrorism -- The threat within: shaping a force for the future.
Includes bibliographical references (pages 223-229) and index.
JSTOR
Keywords: National security -- United States; United States -- Military policy; World politics -- 1989-; Twenty-first century -- Forecasts; Sécurité nationale -- États-Unis.; Politique mondiale -- 1989-; Vingt et unième siècle -- Prévisions.; États-Unis -- Politique militaire; Vingt et unième siècle -- Prévisions.; Military policy; National security; Twenty-first century; World politics; United States; Sicherheitspolitik; Strategie; USA; Veiligheidspolitiek; Militaire politiek; Sécurité nationale -- États-Unis -- 1990- ...; États-Unis -- Relations extérieures -- 1989- ...; États-Unis -- Politique militaire -- 1990- ...; Since 1989; Forecasts